Aspectos fisiológicos e nutricionais de mudas de aroeira e pequi em convivência com capim-braquiarão - Murilo Antônio Oliveira Ruas (2023)
The implantation of Caryocar brasiliense (pequi) and Myracrodruon urundeuva (aroeira) seedlings in forest recovery areas or in intercropped crops faces problems related to competition with weeds. Despite the relevance of the subject, weed competition for these species is little studied, especially when related to coexistence with U. brizantha, considered the main forage crop cultivated in Brazil and a common weed in forest recovery areas. As a result, the objective of this work is to evaluate the competitive aspects and the physiological and initial growth response of C. brasiliense and M. urundeuva seedlings in coexistence with U. brizantha, through two competition experiments, in design and randomized blocks, with six replications, covering each of the tree species kept in coexistence with U. brizantha. In both studies, different densities of the competitor U. brizantha were considered as treatments, being 0 (controls), 14, 28 and 42 individuals/m2, which corresponds to 0, 1, 2 and 3 plants of the competitor/pot. Regarding the results, competition with U. brizantha caused lower instant water use efficiency in the photosynthetic rate of M. urundeuva, with a reduction of up to 35% compared to the absence of the competitor, negatively affecting physiological variables, contents and macronutrient content of M. urundeuva, in its different infestation densities, without interfering, however, in the dry mass production of the seedlings. C. brasiliense plants in competition with U. brizantha, in turn, showed a reduction in photosynthetic rate (45 to 73%), in instantaneous water use efficiency (55 to 70%), in electron transport rate ( 18 to 50%) and in stomatal conductance (40 to 66%) compared to the control, in addition to a reduction (>50%) in the electron transport rate and a small increase in the quantum efficiency of photosystem II, being more efficient in the absorption of macronutrients. Finally, the coexistence of U. brizantha, regardless of density, affected the growth, physiological variables and use of macronutrients of M. urundeuva and C. brasiliense seedlings, proving how harmful the coexistence of U. brizantha is to tree species addressed in this study.